Welding electrode of wood flour fiber glass slag system and preparation method of welding electrode

By using the welding sticks of the wood powder fiber glass residue in the welding stick, the modified nano -zinc powder, the modified white carbon black, and the modified wood powder fiber material are used to solve the existing welding sticks in harsh environments. The problem of poor suspension and difficulty in the protection of melting ponds realized the significant improvement of welding quality and strong adaptability.

CN119347201APending Publication Date: 2025-01-24TIANJIN YONGCHANG WELDING WIRES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411709652.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing welding rods are difficult to meet high performance requirements during oil and gas pipeline construction, especially when welding in harsh environments, the welding slag has poor suspension and difficult molten pool protection, resulting in unstable welding quality.

Method used

Using wooden powder fiber glass residue system, its drug leather formula includes modified nano -zinc powder, modified white charcoal black, and modified wood powder fiber material. Lobricity.

Benefits of technology

Effectively improve the welding process, enhance the arc blowing force and stability, the welding residue is light and easy to suspend, the welding quality is significantly improved, and the adaptability is strong, reducing the problem of post -welding slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119347201A_ABST
    Figure CN119347201A_ABST
Patent Text Reader

Abstract

The invention provides a welding rod of a wood flour fiber glass slag system and a preparation method of the welding rod. A coating is prepared from, by weight, 29.5-30.5 parts of reduced ilmenite, 15-16 parts of ilmenite, 5.0-6.0 parts of silicon manganese alloy, 7-8 parts of albite, 3.5-4.5 parts of calcium mica, 4.5-5.5 parts of 24-mesh mica powder, 5.5-6.5 parts of 70% rutile, 3.5-4.5 parts of 87% rutile, 3-4 parts of 60-mesh marble, 1.0-2.0 parts of refined cotton and 4.5-5.5 parts of white mud. 10-12 parts of modified white carbon black, 6.5-7.5 parts of modified nano zinc powder and 11.5-15.5 parts of a modified wood powder fiber material. According to the welding electrode of the wood flour fiber glass slag system, the welding manufacturability of a traditional welding electrode is effectively improved, circumferential welding of natural gas conveying pipeline steel and vertical downward welding of an oil storage tank are met, the electric arc blowing force is effectively improved, and the electric arc stability is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of welding rods, and in particular relates to a wood powder fiber glass slag welding rod and a preparation method thereof. Background Art

[0002] With the rapid development of social economy, the demand for oil and natural gas in human production and life is increasing, and the transportation of oil and natural gas has become a major issue of concern to people. Among all the current transportation methods, pipeline transportation has become a relatively safe and economical means to meet the demand for oil and natural gas resources. Therefore, pipeline transportation occupies a very important position.

[0003] my country has diverse terrains and geological disasters occur from time to time, posing a serious threat to the safe transportation of oil and gas pipelines. The large-scale displacement of soil caused by landslides causes the pipeline to bend and deform, and in severe cases, it can cause the pipeline to break. The direct impact of falling rocks caused by debris flows on the pipeline can cause instantaneous destruction of the pipeline. Therefore, it is urgent to develop supporting welding rod products with the characteristics of resisting large deformation.

[0004] The welded joint is the weakest link in the pipeline steel, where cracks are most likely to initiate and develop, leading to the failure of the entire pipeline and causing accidents. Therefore, when welding, not only the toughness of the welded joint and the matching degree of the pipe body should be considered, but also the welding performance at the welded joint should be fully paid attention to. At present, the construction environment of such projects is extremely harsh, and slag removal and molten pool protection during welding are difficult, which puts higher requirements on the applicability of welding rods. In order to meet the high performance index requirements of oil and gas pipelines, realize non-destructive testing and good post-weld forming, it is of great significance to develop a new type of wood powder fiber glass slag welding rod in the field of long-distance oil and gas pipelines. Summary of the invention

[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes a wood powder fiber glass slag welding rod and a preparation method thereof.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A wood powder fiber glass slag welding rod, the welding rod comprises a core and a coating, the coating comprising the following raw materials in parts by weight:

[0008] 9.5-30.5 parts of reduced ilmenite, 15-16 parts of ilmenite, 5.0-6.0 parts of silicon-manganese alloy, 7-8 parts of albite, 3.5-4.5 parts of calcium mica, 4.5-5.5 parts of 24 mesh mica powder, 5.5-6.5 parts of 70% rutile, 3.5-4.5 parts of 87% rutile, 3-4 parts of 60 mesh marble, 1.0-2.0 parts of refined cotton, 4.5-5.5 parts of white mud, 10-12 parts of modified white carbon black, 6.5-7.5 parts of modified nano zinc powder and 11.5-15.5 parts of modified wood powder fiber material.

[0009] Furthermore, the preparation method of the modified nano zinc powder comprises the following steps: mixing and stirring the nano zinc powder and potassium sodium water glass under heating conditions to obtain the modified nano zinc powder.

[0010] Furthermore, the nano zinc powder is spherical nano zinc powder; the potassium sodium water glass is low-modulus potassium sodium water glass; the mass ratio of the nano zinc powder to the potassium sodium water glass is 6.5-7.5:28-29; the temperature of the heating step is 48-52° C.; and the time of the mixing and stirring step is 1-3 hours.

[0011] The arc is essentially supplied by the welding power supply. The electron beam moves in a direction and generates a strong and lasting gas discharge phenomenon between the two electrodes. The formula of the coating of the present invention is to achieve the lightness of the welding slag, reduce the proportion of some ore and alloy powders, and to ensure the arc striking and restrike performance of the welding rod, cotton and modified nano zinc powder are added to solve the arc striking conductivity and coating combustion performance, so that the sleeve is effectively protected after the coating is evenly melted.

[0012] Spherical nano zinc powder and low-modulus potassium sodium water glass are physically mixed and stirred for 2±0.1 hours under heating conditions. The electrical double-layer structure of the silicate micelle itself can combine with the particles to form a colloid chain-like zinc silica gel.

[0013] Nano zinc powder as the arc-starting end reinforced positive electrode can produce the following electrochemical reactions:

[0014] Zn+4OH - →Zn(OH)4 2- +2e -

[0015] Zn(OH)4 2- →ZnO+2OH - +H2O

[0016] O2+2H2O+4e - →4OH -

[0017] The overall electrochemical reaction is:

[0018] 2Zn+O2→2ZnO

[0019] The carbon powder produced by the cotton combustion can also ensure the reducibility of the molten pool and further catalyze the forward reaction under high temperature conditions:

[0020] C+2ZnO=2Zn+CO2

[0021] Furthermore, the preparation method of the modified silica comprises the following steps: roasting the silica, and then naturally cooling the silica to room temperature to obtain the modified silica.

[0022] Furthermore, the temperature of the calcination step is 610-630° C. and the time is 1-3 hours; the heating loss of the modified silica is ≤0.5%, and the burning loss is ≤2%.

[0023] In order to achieve slag suspension during welding, modified silica is added, resulting in a smooth glassy slag after welding. Conventional manufacturing methods are gas phase method and precipitation method, and the appearance is generally amorphous and porous. After high-temperature baking, it will partially decompose. In order to avoid the release of gas during the drying process and cause apparent foaming problems, it must be pre-treated by baking before use. After adding modified silica, the following reactions occur in the arc column area during welding:

[0024] R2O·nSiO2=R2O+nSiO2;

[0025] SiO2+2Fe=Si+2FeO

[0026] C+FeO=Fe+CO↑

[0027] The generated CO gas joins the reaction during the droplet transition process, and the combustion increases the blowing force and carries the slag to overflow. The molten state delays the cooling rate of the molten pool, refines the molten metal ripples, covers the weld under the premise of ensuring good fluidity of the slag, and is fully separated and suspended on the surface of the molten pool in a glassy state to facilitate the stripping of the slag shell after welding.

[0028] Furthermore, the preparation method of the modified wood powder fiber material comprises the following steps: mixing elm powder, corn cob fiber and hydroxyethyl cellulose in a water bath to obtain the modified wood powder fiber material.

[0029] Furthermore, the mass ratio of the elm powder, corn cob fiber and hydroxyethyl cellulose is 3.5-4.5:6-7:2-4; the temperature of the water bath step is 80-90° C., the humidity is 78-82%, and the time is 11-13 hours.

[0030] In order to achieve single-sided welding, double-sided forming and all-position welding, modified wood powder fiber materials are added to increase the arc blowing force while ensuring that the arc is stable and concentrated. To meet this demand, elm powder, corn cob fiber and HEC cellulose powder are selected to work together.

[0031] The elm powder, corn cob fiber and HEC cellulose powder are placed in a water bath reactor to interact with each other to achieve a warm water cross-linking process, break the hydrogen-oxygen bonds on some carbon chains, and hydrolyze and reorganize the substituents to complete the addition polymerization reaction.

[0032] (C6H7O2CH3)n+(C6H 10 O5)n+nH2O→[C5H7O2CH2-CH2C5H 10 O6]n

[0033] C 47 H6N+(C2H6O2)n+nH2O→[CH3O-(CHO-C 45 H6N-CH2)-CH2O]n

[0034] The advantage of warm water cross-linking is that it can be carried out at a lower temperature, avoiding changes in material properties that may be caused by high temperature, while not affecting the dispersibility and chemical stability of the material.

[0035] Elm powder, corn cob fiber and HEC cellulose ensure compatibility during the mixing process and show thickening and adsorption properties. They are emulsified into a chain structure, aggregated and adsorbed, reducing the molecular surface tension. The gelation temperature of the polymer product can be increased to 220°C, with a degree of substitution (1.5-2.0), high water retention rate, good fluidity, and enhanced plastic rigidity after air drying and baking, ensuring that the overall arc in the welding process is fierce and concentrated, and the coating is melted for a long time with a uniform burning rate.

[0036] The method for preparing the wood powder fiber glass slag welding rod comprises the following steps:

[0037] Step 1 is to mix the components of the coating evenly, stir and shape them to obtain a mixture;

[0038] Step 2 is to press-coat the mixture on the welding core and bake it to obtain the wood powder fiber glass slag welding rod.

[0039] Furthermore, the ratio of the water glass binder to the coating in step 1 is 23.5-24.5%; the temperature of the baking step in step 2 is 100-129° C. and the time is 20-40 minutes.

[0040] The application of the wood powder fiber glass slag welding rod in the preparation of spiral acid welding rod.

[0041] The reduced ilmenite is grade III reduced ilmenite, wherein the mass content of TiO2 is ≥54%, the mass content of FeO is ≤10%, the mass content of C is ≤0.2%, the mass content of S is ≤0.03%, the mass content of P is ≤0.04%, the particle size is: 24-500 mesh, and the bulk density is ≤2.0g / cm3 (The particles have a dark grey spongy surface).

[0042] The ilmenite is grade II ilmenite, wherein the mass content of TiO2 is ≥55%, the mass content of CaO+MgO is ≤1.0%, the mass content of TFe is ≤33%, the mass content of S is ≤0.02%, the mass content of P is ≤0.04%, the particle size is: 50-500 mesh, and the bulk density is ≤1.5g / cm 3 .

[0043] The silicon-manganese alloy is a grade III silicon-manganese alloy, in which the mass content of Si is 17-20%, the mass content of Mn is ≤65.0%, the mass content of N is ≤0.03%, the mass content of S is ≤0.04%, the mass content of P is ≤0.25%, the mass content of C is ≤1.8%, and the particle size is 80-500 mesh (with red or dark brown color, and no other metals and foreign inclusions are allowed to be mixed).

[0044] The sodium feldspar comprises a SiO2 mass fraction of 64-69%, an Al2O3 mass fraction of 16-22%, a K2O mass fraction of ≤1.0%, a Na2O mass fraction of 9-15%, a S mass content of ≤0.020%, a P mass content of ≤0.050%, a crystal water content of ≤0.60, and a particle size of 60-500 mesh (the powder is white or light yellow).

[0045] The calcium mica has a mass fraction of SiO2 of ≤32%, a mass fraction of CaO of ≥16%, a mass fraction of MgO of ≥18%, a mass content of S of ≤0.04%, a mass content of P of ≤0.020%, a particle size of 10-100 meshes, and a loose specific gravity of ≤0.9 g / cm 3 , sand content ≤2%, slippery, gray or light green in color.

[0046] The mica powder has a mass fraction of SiO2 of 44-50%, a mass fraction of Al2O3 of 20-33%, a mass fraction of K2O+Na2O of ≥7%, a mass content of S of ≤0.020%, a mass content of P of ≤0.020%, a particle size of 20-100 meshes, and a loose specific gravity of ≤0.4 g / cm 3 , sand content ≤2%.

[0047] The 70% rutile, wherein the mass fraction of TiO2 is ≥70%, the mass content of C is ≤0.08%, the mass content of S is ≤0.055%, the mass content of P is ≤0.06%, the particle size is: 40-200 mesh, and the bulk density is ≤2.4g / cm 3 , dark red, brown or black granules.

[0048] The marble has a CaCO3 content of ≥95%, a S content of ≤0.030%, a P content of ≤0.020%, a particle size of 40-500 mesh, and a loose specific gravity of ≥0.9 g / cm 3 ; White particles, without inclusions, impurities or large particles.

[0049] The refined cotton has a particle size of less than or equal to 80 mesh, an ash content of ≤5%, and a loose specific gravity of 0.26-0.28 g / cm 3 ; There should be no acid and sulfur impurities, and no pungent odor.

[0050] The white mud has a mass content of SiO2 of 60-73%, a mass fraction of Al2O3 of 15-25%, a mass content of S of ≤0.050%, a mass content of P of ≤0.050%, a particle size of greater than or equal to 300 meshes, and a loose specific gravity of ≤0.8 g / cm 3 ; The block is light yellow and the powder is grayish white.

[0051] The white carbon black has a mass content of SiO2 of ≥98%, a mass fraction of Fe2O3 of ≤0.50%, a mass content of S of ≤0.01%, a mass content of P of ≤0.015%, H2O≤0.25, a particle size of 100-500 mesh, and no other foreign inclusions may be mixed in.

[0052] The spherical nano zinc powder has a Zn content of ≥99% by mass, an S content of ≤0.03% by mass, a particle size of 150-500 meshes, and a spherical metal crystal structure powder in dark grey.

[0053] The elm powder has a particle size of 60-100 meshes, an ash content of ≤10%, no pungent odor and no other foreign inclusions, and the powder is yellow-brown or reddish-brown.

[0054] The corncob fiber has a particle size of 80-200 meshes, a water content of ≤0.2%, and an ash content of ≤10%; the powder is light yellow.

[0055] The HEC has cellulose ≥90%, adsorbed water ≤5.0, pH value: 6.0-7.0, heat resistance: dark beige after baking at 180±2℃*30min, particle size: 80-500 mesh, whiteness ≥40%, ash content ≤5%, loose specific gravity 0.12-0.20g / cm 3 , in the form of yellow fibrous powder.

[0056] Function of each component:

[0057] Reduced ilmenite grade III and ilmenite grade II: It helps to improve the conductivity of the coating, thereby stabilizing arc combustion. The iron content of more than 30% in the powder can improve the deposition efficiency of welding materials, refine the grains and make the arc soft. During the welding process, the TiO2 in the reduced ilmenite can combine with FeO to form FeO·TiO2, reducing the oxidizability of the slag, thereby improving the anti-porosity ability of the electrode.

[0058] Silicon manganese alloy grade III: transition alloy, deoxidizer, using the chemical affinity between silicon and oxygen to combine deoxidation, containing low ionization elements to enhance arc stability and improve the stability of arc burning.

[0059] Sodium feldspar: It is mainly used for slag formation. It can reduce the basicity of slag, refine the slag particles, and improve the arc stability of the welding rod. When welding with AC voltage at low no-load voltage, its addition ratio can be appropriately increased.

[0060] Calcium mica, 24 mesh mica powder, and white mud: their function is to reduce the oxidizability of the coating and welding slag and remove oxygen from the metal, thereby enhancing the viscosity and plasticity of the coating during the production process and improving the pressure coating performance.

[0061] 70%, 87% rutile: It has the function of adjusting the melting point of welding slag, improving weld formation, refining molten droplets, improving welding process performance and stabilizing the arc.

[0062] 60 mesh marble: slag making and gasification are followed by arc stabilization, adjustment of slag alkalinity and desulfurization and phosphorus removal.

[0063] The following reactions occur under the action of the arc:

[0064] Desulfurization:

[0065] CaCO3→CaO+CO2

[0066] FeS+CaO→CaS+FeO

[0067] Dephosphorization:

[0068] 3CaO+P2O5→Ca3P2O8

[0069] 4CaO+P2O5→Ca4P2O9

[0070] Compared with the prior art, the present invention has the following advantages:

[0071] The wood powder fiber glass slag welding rod of the present invention effectively improves the welding processability of traditional welding rods, meets the requirements of girth welding of natural gas transmission pipeline steel and vertical downward welding of oil storage tanks, effectively improves arc blowing force, ensures arc stability, and has a clear welding molten pool, thin and easy-to-float slag, avoids the problem of slag inclusion in molten metal in all-position welding, improves the good flowability of its slag shell, and the fiber glass slag shell can completely cover it, effectively protecting the welding quality of the weld. In addition, the welding rod has strong operating techniques and environmental adaptability, which improves the welding efficiency of welders to a certain extent.

[0072] The wood powder fiber glass slag welding rod of the present invention has strong operational applicability, and the arc length and weld width can be adjusted at will. It can perform well in harsh outdoor environments, and does not have high requirements on the welder's operating skills. The problem of slag inclusion after welding is basically eliminated during the welding process, and the grinding and rework ratio of engineering welding is greatly reduced, which effectively improves the market competitiveness of the product. The product is non-toxic and harmless, and has no serious impact on the environment and personnel.

[0073] The wood powder fiber glass slag welding rod of the present invention can be used for all-position welding including vertical and downward welding, has strong arc blowing force, can realize single-sided welding and double-sided forming, and has beautiful girth welding pipe joint weld forming; the welding rod improves the welding process defects of the welding rod, the glass slag has good fluidity, evenly covers the weld, and effectively protects the process performance of the deposited metal; the welding rod has good anti-porosity, the wood powder and cellulose enhance the welding arc penetration of the coating, and the organic matter combustion slag is light and easy to float out during the welding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a schematic diagram of a weld bead of a wood powder fiber glass slag welding rod according to Example 1 of the present invention;

[0075] Figure 2 A schematic diagram of a weld bead and weld seam of the welding rod described in Comparative Example 1 of the present invention;

[0076] Figure 3 A schematic diagram of a weld bead and weld seam of the welding rod described in Comparative Example 2 of the present invention;

[0077] Figure 4 A schematic diagram of a weld bead of the welding rod described in Comparative Example 3 of the present invention;

[0078] Figure 5 A schematic diagram of a weld bead and weld seam of the welding rod described in Comparative Example 4 of the present invention;

[0079] Figure 6 A schematic diagram of a weld bead of the welding rod described in Comparative Example 5 of the present invention;

[0080] Figure 7 A schematic diagram of a weld bead of the welding rod described in Comparative Example 6 of the present invention;

[0081] Figure 8 A schematic diagram of a weld bead of the welding rod described in Comparative Example 7 of the present invention;

[0082] Fig. 9 This is a schematic diagram of a welding seam with slag shell falling off of an electric welding rod according to Comparative Example 1 of the present invention;

[0083] Fig.10 This is a schematic diagram of a welding seam with slag shell falling off of an electric welding rod as described in Example 1 of the present invention. DETAILED DESCRIPTION

[0084] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0085] The present invention will be described in detail below with reference to the embodiments.

[0086] In the following examples and comparative examples, 1 part is 1 kg, or other unit weights. Under the same welding molten gold composition conditions, the coating formula shown in the following table is used, and the specific test plan is as follows:

[0087] Table 1 Case welding rod formula ratio (unit: number of parts)

[0088]

[0089] The process parameters for producing water glass in the present invention are low-modulus potassium-sodium water glass with a modulus M of 2.4-2.6 and a concentration Be° in the range of 38-39. The components are mixed evenly and stirred to form, and then the powder is pressed on the welding core by a spiral machine. The welding core used is H08A ordinary low-carbon steel welding core, and the diameter of the welding core is 3.2mm. After pressing, the welding rod directly enters the chain furnace, the outlet temperature is 115±5℃, and the total time is 30±1 minutes. The addition ratio of water glass in the production of welding rods is 23.5-24.5% of the weight of the coating powder.

[0090] The welding rods prepared in each embodiment and each comparative example were subjected to welding experiments. The welding process parameters were as follows: current: 110-140A; layer temperature: 130-150°C; number of layers: 7-9 layers. The chemical composition, mechanical properties of the weld metal and the composition of the weld slag are shown in Tables 2 and 3.

[0091] Table 2 Chemical composition and mechanical properties of deposited metal

[0092]

[0093] Among them, some trace elements are not listed because there is no clear requirement in the national standard.

[0094] Table 3 Chemical composition of welding slag (%)

[0095]

[0096]

[0097] Among them, some trace elements are not listed because there is no clear requirement in the national standard.

[0098] The welding rods prepared in each embodiment and each comparative example were subjected to welding experiments. The welding process parameters were as follows: current: 120 A; plate welding length: 300 cm; welding width: 1 cm; welding speed: 3.75 cm / s. The test data were recorded and the slag shell coverage, uniformity and unit weight were analyzed, as shown in Table 4.

[0099] Table 4 Welding process evaluation

[0100]

[0101] Note: In terms of ranking order, level 1 is the best and level 10 is the worst.

[0102] Table 5 Comparative test of crack resistance test

[0103]

[0104] Note: The average crack value of the example is 0.53mm, the crack rate is 1.27%, the average crack value of the test is 2.51mm, the crack rate is 6.02%.

[0105] The wood powder fiber glass slag welding rod of the present invention can be known from the above test:

[0106] 1. Example 2 adopts the median value of the formula ratio. Compared with Examples 1 and 3, it has better vertical-down all-position welding effect and stronger arc blowing force. Within the formula definition range, the three groups of examples can achieve the expected effect, excellent single-sided welding and double-sided forming, and beautiful girth welding pipe weld forming. The overall welding process performance is Example 2> Example 3> Example 1> Comparative Example 6> Comparative Example 7> Comparative Example 5> Comparative Example 4> Comparative Example 2> Comparative Example 3> Comparative Example 1.

[0107] 2. The wood powder fiber glass slag welding rod of the present invention, compared with the seven comparison examples, can improve the welding process defects of the welding rod. The glass slag has good fluidity, evenly covers the weld, has stable chemical composition and significantly improved mechanical properties, and effectively protects the process performance of the deposited metal.

[0108] 3. Compared with comparative example 1, embodiment 2 has good anti-porosity, wood powder and cellulose enhance the arc penetration of the coating, and the slag from the combustion of organic matter during the welding process is thin and easy to float out, which effectively avoids slag inclusion in the welding weld and affects the rework caused by abnormal flaw detection.

[0109] 4. Compared with Example 6, Example 2 has comparable sleeve uniformity and arc striking performance. The sample modified with nano-zinc powder has significantly better arc striking performance. Compared with the unmodified Comparative Example 2, the latter has problems such as sticking, arc striking failure, and difficulty in restriking. However, the slag water fluidity and weld slag removal properties of the two groups are poor, and the presence of pores makes it impossible to provide good protection for the molten pool.

[0110] 5. Compared with Example 5, Example 2 has equivalent molten pool fluidity and slag shell coverage, but slightly worse arc re-striking performance, and the welding slag is not easy to float out. Compared with the unmodified silica sample 3, the weld surface is porous and not full, and the air permeability and weld slag removal of Example 3 are worse. The slag shell is thick and wide with needle-shaped pores, and some welds have slag inclusions that affect the impact performance.

[0111] 6. Compared with Comparative Example 7, Example 2 has comparable weld slag removal properties, strong and concentrated arc blowing force, and the slag shell is loose and easy to remove after welding, but the slag shell coverage is uneven, and the re-arcing performance is slightly poor. Compared with the unmodified wood powder cellulose sample in Comparative Example 4, the former has better slag suspension, more uniform melting of the welding sleeve, more sufficient combustion blowing force, and better slag shell coverage.

[0112] The weld bead welds of the welding rods of Example 1 and Comparative Examples 1-7 of the present invention are as follows: Figure 1-8 As shown, the slag shell shedding welds of Example 1 and Comparative Example 1 are as follows Figure 9-10 shown.

[0113] Figure 1 The wood powder fiber glass slag of Example 1, Fig.10 The slag shell falls off the weld surface, the welding slag covers evenly, effectively protects the molten metal and improves the mechanical properties, the surface has a glass luster, the welding slag is thin and easy to remove, the weld meat is not easy to oxidize and discolor, and the ripples are clear and beautiful;

[0114] Figure 2 The conventional titanium-calcium type slag system of the welding rod in comparative example 1 is Fig. 9 The slag shell falls off the weld surface. The slag water is relatively thin, and the welding process is easy to flow, resulting in insufficient molding protection, easy to cause pores, welding slag and weld meat aggregation, and severe oxidation on the surface, which is not beautiful.

[0115] Figure 3-Figure 5 The welding seam of the welding rod weld with unmodified powder added has poor overall performance, no obvious difference in slag system, and due to the increase of pores without treatment, there are pressure pits on the surface;

[0116] Figure 6-Figure 8 For the welding seam of the electric welding rod with partially added modified powder, the slag system changes slightly, the slag shell is matte in color, and the welding porosity is significantly improved, but the slag water is too thin and the weld formation is unstable.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A wood powder fiber glass slag welding rod, characterized in that: The welding rod comprises a flux core and a flux coating, wherein the flux coating comprises the following raw materials in parts by weight: 9.5-30.5 parts of reduced ilmenite, 15-16 parts of ilmenite, 5.0-6.0 parts of silicon-manganese alloy, 7-8 parts of albite, 3.5-4.5 parts of calcium mica, 4.5-5.5 parts of 24 mesh mica powder, 5.5-6.5 parts of 70% rutile, 3.5-4.5 parts of 87% rutile, 3-4 parts of 60 mesh marble, 1.0-2.0 parts of refined cotton, 4.5-5.5 parts of white mud, 10-12 parts of modified white carbon black, 6.5-7.5 parts of modified nano zinc powder and 11.5-15.5 parts of modified wood powder fiber material.

2. The wood powder fiber glass slag welding rod according to claim 1, characterized in that: The preparation method of the modified nano zinc powder comprises the following steps: mixing and stirring the nano zinc powder and potassium sodium water glass under heating conditions to obtain the modified nano zinc powder.

3. The wood powder fiber glass slag welding rod according to claim 2, characterized in that: The nano zinc powder is spherical nano zinc powder; the potassium sodium water glass is low-modulus potassium sodium water glass; the mass ratio of the nano zinc powder to the potassium sodium water glass is 6.5-7.5:28-29; the temperature of the heating step is 48-52° C.; and the time of the mixing and stirring step is 1-3 hours.

4. The wood powder fiber glass slag welding rod according to claim 1, characterized in that: The preparation method of the modified white carbon black comprises the following steps: roasting the white carbon black and then naturally cooling it to room temperature to obtain the modified white carbon black.

5. The wood powder fiber glass slag welding rod according to claim 4, characterized in that: The temperature of the calcination step is 610-630°C and the time is 1-3 hours; the heating loss of the modified white carbon black is ≤0.5% and the burning loss is ≤2%.

6. The wood powder fiber glass slag welding rod according to claim 1, characterized in that: The preparation method of the modified wood powder fiber material comprises the following steps: mixing elm powder, corn cob fiber and hydroxyethyl cellulose under water bath conditions to obtain the modified wood powder fiber material.

7. The wood powder fiber glass slag welding rod according to claim 6, characterized in that: The mass ratio of the elm powder, corncob fiber and hydroxyethyl cellulose is 3.5-4.5:6-7:2-4; the temperature of the water bath step is 80-90°C, the humidity is 78-82%, and the time is 11-13 hours.

8. The method for preparing the wood powder fiber glass slag welding rod according to any one of claims 1 to 7, characterized in that: The steps include: Step 1 is to mix the components of the coating evenly, stir and shape them to obtain a mixture; Step 2 is to press-coat the mixture on the welding core and bake it to obtain the wood powder fiber glass slag welding rod.

9. The method for preparing the wood powder fiber glass slag welding rod according to claim 8, characterized in that: The ratio of the water glass binder to the coating in step 1 is 23.5-24.5%; the temperature of the baking step in step 2 is 100-129° C. and the time is 20-40 minutes.

10. Use of the wood powder fiber glass slag welding rod according to any one of claims 1 to 7 in the preparation of spiral acid welding rods.